Understanding the role of climate change in disaster mortality: Empirical evidence from Nepal - Dipesh Chapagain; Luna Bharati; Reinhard Mechler; K.C. Samir; Georg Pflug; Christian Borgemeister (Climate Risk Management)
Climate-related disaster impacts, such as loss of human life as its most severe consequence, have been rising globally. Some studies attribute this increase to population growth, while others point to climate change as the primary cause. However, empirical evidence linking climate change to disaster impacts remains limited, particularly in the Global South. This study addresses the impact attribution question in Nepal, a low-income and highly disaster-prone country. We applied a robust regression-based method that accounts for the role of hazard, exposure and vulnerability in flood and landslide mortality, using subnational scale empirical data from 1992 to 2021.Historically, flood and landslide mortality has been highest in central and eastern Nepal due to the stronger influence of the Indian monsoon. However, disaster impacts have surged in recent years in western Nepal, driven largely by an increase in extreme precipitation events. For example, a one standardized unit increase in maximum one-day precipitation increases flood mortality by 33%, and heavy rain days increases landslide mortality by 45%. In contrast, a one standardized unit increase in per capita income reduces landslide and flood mortality by 30% and 45%, respectively. While reductions in vulnerability have helped lower disaster mortality, population exposure has not played a significant role. Therefore, the rise in flood and landslide mortality, particularly in western Nepal, is primarily attributable to the increase in precipitation extremes linked to climate change. With climate change expected to further intensify such extremes, disaster mortality is likely to increase unless significant efforts are made to reduce vulnerability.